Standard-bearers of equality : America's first abolition movement - Polgar, Paul J. (Omohundro Institute of Early American History and Culture ; University of North Carolina Press, 2019)
"Paul Polgar recovers the racially inclusive vision of America's first abolition movement. In showcasing the activities of the Pennsylvania Abolition Society, the New York Manumission Society, and their African American allies during the post-Revolutionary and early national eras, he unearths this coalition's comprehensive agenda for black freedom and equality"-- Provided by publisher
Keywords: Pennsylvania Society for Promoting the Abolition of Slavery -- History.; New-York Society for Promoting the Manumission of Slaves, and Protecting Such of Them as Have Been, or May Be Liberated -- History.; New-York Society for Promoting the Manumission of Slaves, and Protecting Such of Them as Have Been, or May Be Liberated; Pennsylvania Society for Promoting the Abolition of Slavery; Antislavery movements -- Middle Atlantic States -- History -- 18th century.; Antislavery movements -- Middle Atlantic States -- History -- 19th century.; Free African Americans -- Political activity.; African Americans -- Civil rights -- History.; United States -- Race relations -- History.; Mouvements antiesclavagistes -- États du Moyen-Atlantique (États-Unis) -- Histoire -- 18e siècle.; Mouvements antiesclavagistes -- États du Moyen-Atlantique (États-Unis) -- Histoire -- 19e siècle.; Noirs américains affranchis -- Activité politique.; Noirs américains -- Droits -- Histoire.; États-Unis -- Relations raciales -- Histoire.; HISTORY -- African American.; African Americans -- Civil rights; Antislavery movements; Race relations; Middle Atlantic States; United States; 1700-1899; History